Strategies of Improving CsPbX3 Perovskite Quantum Dots Optical Performance - Wu, Yuejia; Jia, Ruijun; Xu, Jian; Song, Lei; Liu, Yuxin; Zhang, Yuman; Ullah, Shahid; Dai, Jun (Frontiers in Materials, 2022)
All-inorganic perovskite quantum dots (QDs) (CsPbX3, X = Cl, Br, I) become promising candidate materials for the new generation of light-emitting diodes for their narrow emission spectrum, high photoluminescence quantum yield, and adjustable emission wavelength. However, the perovskite QDs materials still face instability against moisture, high-temperature, and UV-light. Many strategies have been reported to improve the photoluminescence (PL) performance of QDs while increasing their stability. These strategies can be divided into three main categories: doping engineering, surface ligand modification, coating strategies. This paper reviews the recent research progress of surface ligands, inorganic and polymer coating, and metal ions doping of CsPbX3 QDs. Partial substitution of Pb2+ with non-toxic or low-toxic metal ions can improve the formation energy of the perovskite lattice and reduce its toxicity. The surface polymer modification can use their ligands to bond with the uncoordinated lead and halogen ions on perovskite QDs surface to reduce surface defects, thereby improving the PL intensity and stability. In addition, the organic or inorganic coating materials on perovskite QDs can effectively avoid their contact with the external environment, thereby improving the stability of the perovskite. The optical properties of the modified QDs, including transient absorption spectra, temperature-dependent PL spectra, time-resolved photoluminescence (TRPL) spectra properties, etc. were discussed to explain the physical mechanism. The potential applications of all-inorganic perovskite QDs as down-conversion fluorescent materials in light-emitting diodes are presented. Finally, we provide some possible methods to further improve the PL performance of the all-inorganic perovskite QDs.